2022
DOI: 10.1002/ana.26526
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Neuron Prokineticin‐2 as a Potential Target in Parkinson's Disease

Abstract: Objective The objective of this study was to outline the dynamics of prokineticin‐2 pathway in relation to clinical‐pathological features of Parkinson's disease by examining olfactory neurons of patients. Methods Thirty‐eight patients (26 de novo, newly diagnosed) and 31 sex/age‐matched healthy controls underwent noninvasive mucosa brushing for olfactory neurons collection, and standard clinical assessment. Gene expression levels of prokineticin‐2, prokineticin‐2 receptors type 1 and 2, and prokineticin‐2‐long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…We found that estradiol levels were higher in patients at the beginning of the disease and in those with milder motor impairment or lesser impact of motor fluctuations, consistent with the well-known protective effect of estradiol, as seen in female patients [20] and animal models [23]. The reasons underlying the decline of estradiol levels along the disease course cannot be established here, but it may shape other protective or compensatory mechanisms, weakening along the PD clinical-pathological progression [24].…”
Section: Discussionsupporting
confidence: 81%
“…We found that estradiol levels were higher in patients at the beginning of the disease and in those with milder motor impairment or lesser impact of motor fluctuations, consistent with the well-known protective effect of estradiol, as seen in female patients [20] and animal models [23]. The reasons underlying the decline of estradiol levels along the disease course cannot be established here, but it may shape other protective or compensatory mechanisms, weakening along the PD clinical-pathological progression [24].…”
Section: Discussionsupporting
confidence: 81%
“…In particular, because efficient ONs mitochondria are critical for proper olfactory signalling ( Fluegge et al, 2012 ), we could hypothesize that PK2, by the stimulation of mitochondrial activity, may improve olfaction, counteracting detrimental effects of chronic inflammation and SP, which instead aggravate oxidative stress and mitochondrial impairment ( Wang et al, 2014 ). Indeed, the potential of PK2 as a neuroprotective mediator has been recently presented in Parkinson’s disease, where patients at the early stages of the disease exhibit increased levels within the ONs ( Schirinzi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…All participants underwent non-invasive olfactory mucosa brushing for ONs collection by expert otolaryngologists as described in ( Brozzetti et al, 2020 , Schirinzi et al, 2022 , Stefani et al, 2021 ). After inspection of the nose under nasal endoscopic view, ONs were collected through a specifically designed flocked nasal brush (FLOQBrushTM, Copan Italia Spa, Brescia, Italy).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations